How the Accessibility in E-Commerce Affects the Inclusion of the Visually Impaired? Visually impaired internet users in developing countries - Sosa, Emilio; Villegas-Mateos, Allan (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2021)
This study reviews the public policy effectiveness of website accessibility in Mexico and explains how these regulations may affect the visually impaired. The authors did n=6 semi-structured interviews with key players of the visually disabled community and then evaluated n=366 websites with a web scraping tool, using principal components analysis and non-parametric statistics to compare their accessibility by type of website. The authors found that even if there is a regulation for providing equal access to websites, the state of the law is insufficient and non enforced for private and public institutions, affecting the basic human right for visually impaired internet users.